Need more love - Kominsky-Crumb, Aline 1948-2022 (MQP, 2007)
Aline Kominsky-Crumb, one of the earliest female cartoonists, presents a collection of her own highly inventive and daring artwork from over four decades, along with unusual photographs and memorabilia. The road to becoming an underground- comics legend begins with Komisky-Crumb as a nice jewish girl from Long Island, carries her to Greenwich Village in the 1960's, and to California, land of hippy cartoonists, and on to a more or less sedate life with hubby(equally legendary R. Crumb) and daughter, Sophie. Her funny/sad tales show a woman bewildered by her place in society and determined to find her own way. These stories touch on every phase of her existence from childhood, to sexual obsessions, food, motherhood and, of course, her art. The book includes sharp vignettes of the Movers and Shakers - and the jerks - of the art and music worlds since the sixties
Keywords: Kominsky-Crumb, Aline -- 1948-; Women cartoonists -- United States -- Biography -- Comic books, strips, etc; Cartoonists -- United States -- Biography -- Comic books, strips, etc; Untergrundliteratur; USA; Biografie; Comic